PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING MENGGUNAKAN MOODLE BERBASIS E-MODUL PADA PEMBELAJARAN INTALASI PENERANGAN LISTRIK UNTUK KELAS XI TITL SMK SWASTA IMELDA MEDAN - Feber Dhika Purba; Hamonangan Tambunan (Universitas Negeri Medan, 2021)
Abstract This study aims to know the feasibility of media, as well as to know the response to the development of e-learning media using moodle-based e-modules on the learning of electrical lighting installations at SMKS Imelda Medan. This e-learning development uses addie development model adapted from Mollenda and Reiser (2003). namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. E-learning feasibility assessment is conducted by material experts, media experts, and teachers as respondents. Data collection techniques used are questionnaire techniques to obtain quantitative data as primary data and qualitative data in the form of suggestions or comments as data for e-learning improvements. Quantitative data obtained is then converted into qualitative data using ideal assessment criteria. The results showed that: e-learning has